The efficacy of computer reminders on external quality assessment for point-of-care testing in Danish general practice: rationale and methodology for two randomized trials - Felding Peter; Mosbæk Niels; Nielsen Anette; Kousgaard Marius; Ertmann Ruth; Siersma Volkert; Waldorff Frans B; Hjortsø Else; Reventlow Susanne (Implementation Science, 2011)
Abstract Background Point-of-care testing (POCT) is increasingly being used in general practice to assist general practitioners (GPs) in their management of patients with diseases. However, low adherence to quality guidelines in terms of split test procedures has been observed among GPs in parts of the Capital Region in Denmark. Computer reminders embedded in GPs electronic medical records (ComRem) may facilitate improved quality control behaviour, but more research is needed to identify what types of reminders work and when. The overall aim of this study is to evaluate the efficacy of ComRem to improve GPs adherence to quality guidelines. This article describes the rationale and methods of the study that constitute this research project. Methods/design The study is conducted as two randomised controlled trials (RCTs) among general practices in two districts of the Capital Region in Denmark. These districts contain a total of 739 GPs in 567 practices with a total of 1.1 million patients allocated to practice lists. In the first RCT (RCT A), ComRem is compared to postal reminder letters. In the second RCT (RCT B), ComRem is compared to usual activities (no reminders) with a crossover approach. In both of these studies, outcomes are measured by the number of split tests received by the laboratory. Conclusions This study will contribute to knowledge on the efficacy of ComRem in primary care. Because the study does not explore GPs' perceptions and experiences with regard to ComRem, we will subsequently conduct a qualitative survey focusing on these aspects. Trial registrations Study A: ClinicalTrials.gov identifier: NCT01152151 Study B: ClinicalTrials.gov identifier: NCT01152177